Dichorionic triamniotic triplets after two blastocysts transfer underwent multifetal pregnancy reduction: two case reports and literature review - Qianhua Xu; Min Li; Xiaolei Wang; Hedong Lu; Weiwei Zou (BMC, 2024)
Abstract Background The increase in the rate of multiple pregnancies in clinical practice is associated with assisted reproductive technology (ART). Given the high risk of dichorionic triamniotic (DCTA) triplet pregnancies, reducing DCTA triplet pregnancies to twin or singleton pregnancies is often beneficial. Case presentation This article reports on two cases of DCTA triplet pregnancies resulting from two blastocyst transfers. Given the high risk of complications such as twin-to-twin transfusion syndrome (TTTS) in monochorionic diamniotic (MCDA) twin pregnancies, patients have a strong desire to preserve the dichorionic diamniotic (DCDA) twins. Multifetal pregnancy reduction (MFPR) was performed in both cases to continue the pregnancy with DCDA twins by reducing one of the MCDA twins. Both of the pregnant women in this report eventually gave birth to healthy twins at 37 weeks. Conclusions For infertile couples with multiple pregnancies but with a strong desire to remain the DCDA twins, our report suggests that reducing DCTA triplets to DCDA twin pregnancies may be an option based on clinical operability and assessment of surgical difficulty.